Shared idiotypes are expressed on mouse and human anti-DNA autoantibodies. - Morgan, A (1985)
The expression of common idiotypes on human and mouse anti-DNA monoclonal autoantibodies made by hybridomas was examined by their competitive binding to anti-idiotype antibodies. Some murine autoantibodies inhibited the binding of a human anti-DNA autoantibody 16/6 to monoclonal or polyclonal anti-idiotypic antibodies. Another human antibody (134) was not inhibited in its binding to homologous anti-idiotypic antibodies. The expression of the human 16/6 idiotype on mouse antibodies was restricted to those that had a specificity similar to the 16/6 antibody itself, their major properties being that they reacted more strongly with single stranded DNA (ssDNA) than double stranded DNA (dsDNA). One mouse antibody expressing the 16/6 idiotype also bound weakly to RNA. The results imply structural similarities between the binding sites of the antibodies in the two species, and are consistent with evolutionary conservation of V genes coding for primitive ancestral antibodies that react with DNA and become diversified through somatic mutation.